Cluster Based Communication In Wsn: A Survey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
WSN establishes an essential role in industrial applications. WSN consists of multiple tiny sensor nodes (SNs), which are organized   in an outlying area.These sensor nodes consist of battery and thus it’s very challenging to interchange these SNs in a brassy environment once deployed.Therefore, in order to increase the network life, the sensor node energy needs to be preserved. Thus, in some protocols these wsn’s nodes grouped to form a cluster for efficient communication. In hierarchical approach,there aretwo concepts- one based on cluster and other one based on grid concepts. In cluster-based concepts, SN’s assembled to form clusters, where nodes having more residual energy become a leader of the cluster and thus known as Cluster Head. Thus, the network is separatedinto virtual grids in case of a grid based concept. This paper discusses the hierarchical routing protocol, its design challenge andan advantages and disadvantages of protocols.